A Case of Urethral Diverticulum with Surgical Repair Using Cadaveric Pericardial Tissue - Loren Custer; Morris Jessop; Stanley Zaslau; Robert Shapiro (Case Reports in Urology)
A urethral diverticulum is a relatively uncommon finding. The estimated prevalence is approximately 1-5% in the general population. While the definitive treatment is surgical correction, there are limited studies guiding the best approach to repair. This is the case of a 48-year-old female who initially presented with vaginal discharge, dysuria, and dyspareunia. MRI revealed the diagnosis of suspected urethral diverticulum. The patient was treated with surgical correction with the aid of needle localization prior to the procedure. After the diverticulum was excised, the resulting defect in the urethra was successfully closed with cadaveric pericardial tissue. A urethral diverticulum should be considered in the differential diagnosis when a patient presents with symptoms such as recurrent urinary tract infections (UTIs) vaginal mass, dysuria, dyspareunia, or vaginal discharge. The use of cadaveric tissue augments the surgical technique for repair.